Reimagining Myths: A Study of Contemporary Fictional Retellings of Surpanakha - Puja, S (Feminist theology, 2026)
Myths are more than literary plots and themes; they provide insights into social structures and the human psyche, particularly regarding women’s roles across various cultures and historical periods. This study explores how myths, specifically those embedded in the epic Ramayana, can be retold to challenge patriarchal norms. In Stealing the Language, Alicia Ostriker describes revisionist myth-making as repurposing ancient figures to drive cultural change. This study scrutinizes contemporary interpretations of Surpanakha in The Liberation of Sita by Volga and Lanka’s Princess by Kavita Kane. It investigates how these authors reconfigure Surpanakha from a simplistic antagonist into a complex character endowed with aspirations and agency. Employing Uma Chakravarti’s notion of ‘Revisionism’, the analysis explores the narrative’s attempts to humanize Surpanakha and liberate her from patriarchal constraints. The paper underscores the authors’ efforts to elevate Surpanakha from marginalization to prominence. It also examines how these authors portray Surpanakha’s emotional depth and reimagine her fate, thereby challenging traditional Ramayana narratives and patriarchal representations, while offering new perspectives on empowering marginalized voices.